2020
DOI: 10.1016/j.apmr.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Microbiota of the Physiotherapist's Environment

Abstract: Interventions: A microbiological sampling was carried out in the physiotherapy centers. The samples were studied using the usual culture and analysis methodology for characterization and isolation of a range of bacteria. Main Outcome Measures: Absolute and relative frequency of microorganism isolation. Results: In the analysis, pathogens normally responsible for nosocomial infections were detected, especially on instruments and equipment used by the physiotherapist such as sponge electrodes, and were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…They performed sampling from the hands of physiotherapists without previously informing them to prevent influencing their behavior (hand washing in particular). The majority of the detected microorganisms were gram-positive bacteria, in accordance with the usual microbiota of the human body, suggesting the necessity of reinforcing hand washing or even combining hand washing with the use of gloves to reduce the transmission of these bacteria among different patients ( 53 ).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…They performed sampling from the hands of physiotherapists without previously informing them to prevent influencing their behavior (hand washing in particular). The majority of the detected microorganisms were gram-positive bacteria, in accordance with the usual microbiota of the human body, suggesting the necessity of reinforcing hand washing or even combining hand washing with the use of gloves to reduce the transmission of these bacteria among different patients ( 53 ).…”
Section: Resultsmentioning
confidence: 82%
“…In addition to these bacteria, Pérez-Fernández et al identified other important pathogens, such as Staphylococcus aureus , Acinetobacter spp, and Escherichia coli on the sponge electrode. In this study, sponge electrodes represented the instrumental samples with higher and more varied contamination, up to more than 20 different bacterial species, probably as the consequence of inadequate cleaning ( 53 ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations